Nevsky Forum: section "Crisis of confidence in the modern legal order" (St. Petersburg, June 2021) - N. V. Razuvaev; I. K. Shmarko (Теоретическая и прикладная юриспруденция)
On June 26, 2021, within the framework of the Nevsky Forum, at the Faculty of Law of the NWIM of RANEPA, the section "Crisis of confidence in the modern legal order: threats and ways to overcome" was organized. Russian and foreign scientists and practicing lawyers took part in the discussion, discussed such problems as the transformation of the principles of the rule of law in the age of postmodernity, political and legal threats to the stability of the rule of law, means of developing a dialogue between the state and the individual, tools of legal communication in the context of digitalization.